Study guides

Q: 2x2 - 3x plus 7

Write your answer...

Submit

Related questions

d/dx 2x2+3x+7=4x+3

(2x + 7)(x - 2)

2x2 + 3x + 1 = (x + 1)(2x + 1)

(x-2)(2x+7)

65

(2x + 7)(x - 2)

(2x + 7)(x - 2)

x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)

-11

2x2 + 3x - 20 = (x + 4)(2x - 5).

This expression could be reordered as 1 + 3x + 2x2.

7

No.

If: 2x2-3x+1 = 0 Then: x = 1 or x = 1/2

No. You'd have to use the ABC-formula

x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

(x-1)(2x+5)

(2x + 1)(x + 1) so x = -0.5 or -1

=3x+7

The discriminant is 1.

10x + 7 + 3x = 13x + 7

(-3x - 1)(3x - 7)

2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.

38*4 + 3 + 7 - 3x = 162 - 3x